2014
DOI: 10.1186/ar4674
|View full text |Cite
|
Sign up to set email alerts
|

Increase of nerve growth factor levels in the human herniated intervertebral disc: can annular rupture trigger discogenic back pain?

Abstract: IntroductionNerve growth factor (NGF) has an important role in the generation of discogenic pain. We hypothesized that annular rupture is a trigger for discogenic pain through the action of NGF. In this study, the protein levels of NGF in discs from patients with disc herniation were examined and compared with those from discs of patients with other lumbar degenerative disc diseases.MethodsPatients (n = 55) with lumbar degenerative disc disease treated by surgery were included. Nucleus pulposus tissue (or hern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 47 publications
1
19
1
6
Order By: Relevance
“…Studies have showed various types of activated immunocytes and inflammatory factors were recruited in NP-nerve root area [62,63]. The immunocytes were identified including macrophages, T cells, B cells, NK cells and mast cells, and the inflammatory factors were detected such as phospholipase A2 [64], leukotrienes [65], fibroblast growth factor [66], the IL family [66], tumor necrosis factors [67], matrix metalloproteinases [68], nitric oxide [69], substance P [70], monocyte chemoattractant protein-1 [71], vascular endothelial growth factor [72] and nerve growth factor [73]. These factors constitute a complicated region contributing to the immune stress of the nerve root.…”
Section: Implications For Clinical Management Of Ivd Degenerationmentioning
confidence: 99%
“…Studies have showed various types of activated immunocytes and inflammatory factors were recruited in NP-nerve root area [62,63]. The immunocytes were identified including macrophages, T cells, B cells, NK cells and mast cells, and the inflammatory factors were detected such as phospholipase A2 [64], leukotrienes [65], fibroblast growth factor [66], the IL family [66], tumor necrosis factors [67], matrix metalloproteinases [68], nitric oxide [69], substance P [70], monocyte chemoattractant protein-1 [71], vascular endothelial growth factor [72] and nerve growth factor [73]. These factors constitute a complicated region contributing to the immune stress of the nerve root.…”
Section: Implications For Clinical Management Of Ivd Degenerationmentioning
confidence: 99%
“…Nerve growth factor (NGF), one of the neurotrophic factors, is involved in pain related to IVD degeneration [46] and herniation [2]. It has been reported that herniated NP also increases production of brain-derived neurotrophic factor (BDNF) in pain-processing neurons [34], which can correlate with pain sensitivity in the rat model [15,16,41,45].…”
Section: Introductionmentioning
confidence: 99%
“…Aoki et al demonstrated using a new detailed VAS system that nonspecific LBP in elderly patients was present in motion, besides during standing and sitting 18) . Recently, LBP in motion was related to an increase in the nerve growth factor level in the intervertebral disc, which led to discogenic LBP 19) . Some authors reported that walking-induced LBP 20) and the LBP with the neuropathic component 21) had better response to pregabalin known as a therapeutic agent for neuropathic pain.…”
Section: Kalichman Et Al Reported In the Framinghammentioning
confidence: 99%